Nanoporous Carbons: Superior Multifunctional Activity of Nanoporous Carbons with Widely Tunable Porosity: Enhanced Storage Capacities for Carbon‐Dioxide, Hydrogen, Water, and Electric Charge (Adv. Energy Mater. 9/2020). Issue 9 (3rd March 2020) - Gadipelli, Srinivas; Howard, Christopher A.; Guo, Jian; Skipper, Neal T.; Zhang, Hong; Shearing, Paul R.; Brett, Dan J. L.
Abstract : In article number 1903649, Srinivas Gadipelli and co‐workers present detailed insights for the efficient physical adsorption of guest species (molecules and ions) in nanoporous carbons with engineered pore‐widths (eNPCs). The superior storage capacities for carbon‐dioxide, hydrogen, water and electric charge with related porosity characteristics are systematically demonstrated by designing eNPCs from biomass pine‐cones, coffee‐grounds, and graphene‐oxide and metal‐organic frameworks.